Crystal Structure of CYP106A2 in Substrate‐Free and Substrate‐Bound Form. (11th March 2016) - Janocha, Simon; Carius, Yvonne; Hutter, Michael; Lancaster, C. Roy D.; Bernhardt, Rita
Abstract: CYP106A2 from Bacillus megaterium ATCC 13368 is known as a bacterial steroid hydroxylase that is also capable of hydroxylating a variety of terpenoids. To analyze the substrate specificity of this enzyme further, different resin acids of the abietane and pimarane types were tested with regard to binding and conversion. Product formation could be shown for all tested substrates. Spectroscopic studies revealed type I binding spectra for isopimaric acid, but dehydroabietic acid did not induce a high‐spin shift of the enzyme. Interestingly, binding of abietic acid resulted in a type II difference spectrum typical for nitrogenous inhibitors. Co‐crystallization of CYP106A2 with abietic acid and structure determination revealed bending of the heme cofactor when abietic acid was bound in the active site. Quantum chemical calculations strongly suggest that this heme distortion is the cause of the unusual spectroscopic characteristics. Abstract : Substrate binding in a cytochrome P450 of the 106 family : CYP106A2 is capable of hydroxylating a variety of resin acids, one of which is abietic acid. Interestingly, binding of this substrate results in a type II difference spectrum, which is typical for inhibitors. Quantum chemical calculations strongly suggest that this effect is caused by a distortion of the heme cofactor after binding of abietic acid.